2016
DOI: 10.15269/jksoeh.2016.26.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Depression among Wage Earners by Subjective Health and Stress Perception

Abstract: Objectives: The purpose of this study is to analyze factors associated with depression among wage earners by subjective health and stress perception. Methods: The study subjects include 1,787 wage earners(aged 19 and older) who are currently working, using data from the 2014 National Health and Nutrition Survey. Data were analyzed using frequency test, t-test, ANOVA and multiple regression. Results: Multiple regression analysis showed that perceived stress level, subjective health status, age, monthly househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
4
0
0
Order By: Relevance
“…The analysis of personal income related to depression showed that lower personal income for both daytime and shift workers corresponded to higher levels of depression. This is consistent with previous studies which have found that lower income groups experience higher levels of depression [27][28][29]. In addition, this study found differences in depression levels according to personal income were greater among shift workers than among daytime workers.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The analysis of personal income related to depression showed that lower personal income for both daytime and shift workers corresponded to higher levels of depression. This is consistent with previous studies which have found that lower income groups experience higher levels of depression [27][28][29]. In addition, this study found differences in depression levels according to personal income were greater among shift workers than among daytime workers.…”
Section: Discussionsupporting
confidence: 93%
“…This is somewhat consistent with the results of a study on paid workers that showed higher rates of depression among younger workers, especially those between 19 and 39 years old [27]. The high level of depression among workers aged 19 to 39 years compared to other age ranges reflects the socioeconomic environment of South Korea, where there has been an increase in youth unemployment, nontraditional employment, and job insecurity [27]. In addition, people in their 30s often experience a new family environment due to getting married and having chil- The reference groups for dummy variables were as follows: age (≥60 years), personal income (high), marital status (married), perceived health status (good), smoking status (no), cancer screening (yes), unmet medical needs (no), and unmet dental needs (no).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations